An Initiative to the Project Based Learning at KGRCET:As a Part of Active Learning Methodologies - Sandhya, Tuti; Anusha, P. (Journal of Engineering Education Transformations, 2025)
Designing problems for project based learning (PBL) courses in engineering education has always a challenging task; PBL is a model for teaching, problem solving and is a highly operative technique for engineering pedagogy, which is to learn design by experimenting design as active percipients. This paper describes pedagogical issues involved in conducting the PBL Activity in Embedded System course, designing a problem in course, and analysis of students’ solutions. It also presents the assessment of PBL in engineering education along with characteristics, Benefits, problems and differences between traditional and PBL approaches.